Structure Shift of Noun Phrases in "The Story of An Hour" and Its Translation "Kisah Satu Jam" - Putra, I Putu Rama; Widhiarcani Matradewi, Ni Ketut; Sumaryana Putra, I Komang (Humanis, 2022)
One of the short stories that is rather popular among teenagers and adults is The Story of An Hour by Kate Chopin in 1894. When reading the translation of the story, there are various translation shifts that can be found, especially the structure shift which is the type that most often occurs in the world of translation because every language has its own grammatical structure. Therefore, this study intended to analyze noun phrases that represent structure shifts using the theory of translation shift by Catford (1965) and the theory of noun phrases by Quirk and Greenbaum (1985). The data were collected using note-taking and observation method which were analyzed descriptively and qualitatively in the form of words and language. This study found two types of noun phrases that represent structure shifts, namely: three data were classified as simple noun phrases and four data were classified as complex noun phrases